The plague and I - MacDonald, Betty Bard (University of Washington Press, 2016)
Getting tuberculosis in the middle of your life is like starting downtown to do a lot of urgent errands and being hit by a bus. When you regain consciousness you remember nothing about the urgent errands. You cant even remember where you were going. Thus begins Betty MacDonald's memoir of her year in a sanatorium just outside Seattle battling the White Plague. MacDonald uses her offbeat humor to make the most of her time in the TB sanatorium making all of us laugh in the process.